2021
DOI: 10.1155/2021/8717565
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of RIP3 Improves the Protective Effect of ATF6 in an Acute Liver Injury Model

Abstract: Background. Activating transcription factor 6 (ATF6) and receptor-interacting protein 3 (RIP3) are important signaling proteins in endoplasmic reticulum (ER) stress and necroptosis, respectively. However, their regulatory relationship and clinical significance are unknown. We investigate the impact of ATF6 on RIP3 expression, and its role in hepatocyte necroptosis in an acute liver injury model. Methods. In vivo and in vitro experiments were carried out. LO2 cells were treated with thapsigargin (TG). In vivo, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…In the study, we discovered the reduction of CHOP and Grp78 protein levels and Ca 2+ concentration and the rise of SW620 cell proliferation, which demonstrated that knockdown of ATF6 partially negated the proapoptotic effect of curcumin on CRC cells. In a mouse experiment, necroptosis, liver damage, and ER stress are greatly stifled in mice with ATF6 knockdown (Huang et al., 2021). More convincingly, the raised expression of ATF6 in cervical cancer cells is associated with increased proliferation and decreased apoptosis (Liu et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the study, we discovered the reduction of CHOP and Grp78 protein levels and Ca 2+ concentration and the rise of SW620 cell proliferation, which demonstrated that knockdown of ATF6 partially negated the proapoptotic effect of curcumin on CRC cells. In a mouse experiment, necroptosis, liver damage, and ER stress are greatly stifled in mice with ATF6 knockdown (Huang et al., 2021). More convincingly, the raised expression of ATF6 in cervical cancer cells is associated with increased proliferation and decreased apoptosis (Liu et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…ER stress can also activate NF-κB to enhance TNF-α expression and necroptosis ( 66 - 68 ). Our previous studies have shown that ER stress enhances hepatocyte necroptosis during acute liver injury ( 32 ) and activates ATF6 to partially alleviate hepatocyte necroptosis ( 69 ). ATF6 is an ER stress sensor and transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, ATF6 alleviated necroptosis through upregulating AFP in liver injury ( 70 ). However, it also upregulated RIP3 expression, which did not alleviate necroptosis of liver cells ( 69 ). Therefore, although ATF6 alleviates hepatocyte necroptosis during liver injury, its specific regulatory effect is extremely complex and remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that ATF6 is important for hepatocyte apoptosis and programmed necrosis[ 40 ]. It is possible that intracellular AFP may interact with intracellular proteins, transcription factors, kinases, co-activators and cell cycle regulators, such as PTEN to activate the PI3K/AKT/mTOR signaling to support the hepatocyte survival[ 41 ].…”
Section: Discussionmentioning
confidence: 99%